Topical application of Acacia nilotica pods' water extract enhances wound healing in Sprague-Dawley rats by alleviating oxidative stress and suppressing pro-inflammatory cytokines - Kankara, Sulaiman Sani; Sani, Dahiru; Mustafa, Muskhazli; Ibrahim, Mohd Hafiz; Go, Rusea (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
This study was conducted to validate the folkloric use of Acacia nilotica pods as wound healing agent. Full thickness excision wounds of 6mm diameter were created on Sprague-Dawley rats. Prior to the wound healing assessment, the antioxidant activity of the extract was determined in vitro using 2,2ꞌ- diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. Six groups of 6 wounded rats were formed. In each group, the wounds were topically treated with either petroleum jelly (vehicle control), silver sulfadiazine (positive control), 0.5%, 1% or 2% Acacia nilotica cream (treatment groups) prepared by mixing appropriate quantity of A. nilotica pods’ aqueous extract with petroleum jelly. The negative control group received no treatment. The wound healing parameters assessed include wound contraction rate, level of pro-inflammatory cytokines Interleukin1β (IL-1 β) and Tumor Necrosis Factor-α (TNF- α) and histopathological analysis of the wound area. Wounds were assessed on 7th and 14th post wounding days. The extract showed a good, dose dependent DPPH-radical scavenging activity comparable to trolox. Topical application of A. nilotica cream significantly (P< 0.05) enhances wound contraction rate compared to the control groups in both 7th and 14th days of evaluation. The extract also significantly suppressed the expression of both IL-1β and TNF-α in dose dependent manner throughout the study period. The histological analysis revealed that the extract treatment enhanced cellular proliferation as evident by the increased capillary vessels, re-epithelization and dermal tissues regeneration. Overall study suggest that A. nilotica pods’ water extract promotes wound healing in Sprague-Dawly rats by ameliorating oxidative stress and suppression of pro-inflammatory cytokines. This study validates the folkloric use of A. nilotica pods for postpartum wound healing for the first time. Further studies aimed at identifying and isolating active principles from this plant is recommended.